Pengaruh Cash Coversion Cycle, Networking Capital Terhadap Cash Holding (Studi Empiris Pada Perusahaan Sektor Industri Barang Konsumsi Yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Juardi, Juardi; Mujiani, Sari; Silfianah, Nita; Sari, Sukarni Novita (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2021)
This study aims to determine the effect of cash conversion cycle, net working capital   on cash holding on manufacturing companies in the consumer goods industry sector listed on Indonesia Stock Exchange (IDX). The sampel used in this study is a company listed on the Indonesia. The research period was the period of 2015-2019. The sampel of this study was obtained used a purposive-sampling method where 35 companies met the criteria. This research used secondary data and was analyzed using SPSS 26. The data analysis method used in this research was multiple linear regression analysis. The result showed that cash conversion cycle have a negative and significant on cash holding and net working capital have a positive and significant on cash holding. The ability of independent variables to explain the dependent variable is 40,5% and 59,5% was explained by other variables outside of this study